Rapid evolution of hybrid breakdown following recent divergence with gene flow in Senecio species on Mount Etna, Sicily - Wong, ELY; Nevado, B; Hiscock, SJ; Filatov, DA (Springer Nature, 2022)
How do nascent species evolve reproductive isolation during speciation with on-going gene flow? How do hybrid lineages become stabilised hybrid species? While commonly used genomic approaches provide an indirect way to identify species incompatibility factors, synthetic hybrids generated from interspecific crosses allow direct pinpointing of phenotypic traits involved in incompatibilities and the traits that are potentially adaptive in hybrid species. Here we report the analysis of phenotypic variation and hybrid breakdown in crosses between closely-related Senecio aethnensis and S. chrysanthemifolius, and their homoploid hybrid species, S. squalidus. The two former species represent a likely case of recent (<200 ky) speciation with gene flow driven by adaptation to contrasting conditions of high- and low-elevations on Mount Etna, Sicily. As these species form viable and fertile hybrids, it remains unclear whether they have started to evolve reproductive incompatibility. Our analysis represents the first study of phenotypic variation and hybrid breakdown involving multiple Senecio hybrid families. It revealed wide range of variation in multiple traits, including the traits previously unrecorded in synthetic hybrids. Leaf shape, highly distinct between S. aethnensis and S. chrysanthemifolius, was extremely variable in F2 hybrids, but more consistent in S. squalidus. Our study demonstrates that interspecific incompatibilities can evolve rapidly despite on-going gene flow between the species. Further work is necessary to understand the genetic bases of these incompatibilities and their role in speciation with gene flow.